(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Diabetes is one of the most prevalent diseases worldwide. Self-care practices play an important role in diabetes management and prevention of complications. Demographics, patient knowledge, socioeconomic status, and culture affect self-care practices and, consequently, disease outcomes. This study was conducted to assess self-care practices and determine associations with sociodemographic factors among patients with diabetes. Participants and methods: A purposive sample of 382 patients with type 2 diabetes was assembled for this exploratory study. A semi-structured questionnaire was adapted to serve as a data-gathering tool. Information was collected regarding sociodemographic features, clinical characteristics, and self-care practices related to diabetes management. Continuous variables were analyzed using frequencies and percentages, and categorical variables were analyzed using chi-square tests. Results: In total, 382 questionnaires were completed by 382 patients approached for study enrollment. No standard of diabetes self-care was adhered to by all patients. Indeed, only 28.5% of participants reported receiving a glycated hemoglobin test to inform diabetic treatment planning. Sociodemographic factors of age, sex, marital status, educational level, and monthly household income were associated with adherence to self-care practices among patients with diabetes. Conclusion: Self‑care practices of patients with diabetes are influenced by many sociodemographic factors. Clinically, this information can be applied to design and target education and care planning for patients with type 2 diabetes. Providing special attention to patients with diabetes would allow for the provision of realistic recommendations regarding self-care.